Assessing gut barrier integrity and reproductive performance following pre-mating oral administration of solid-lipid-nanoparticles designed for drug delivery - Lacconi, Valentina; Massimiani, Micol; Antonello, Giulia; Gasco, Paolo; Bernardini, Roberta; Ferrari, Cristiana; Ippoliti, Lorenzo; La Sala, Gina; Pietroiusti, Antonio; Fenoglio, Ivana; Riganti, Chiara; Campagnolo, Luisa (Frontiers in Toxicology, 2025)
Solid lipid nanoparticles (SLNs) have gained interest as drug delivery carriers due to their efficient cellular internalization and increased therapeutic effect of the loaded drug, with minimal side effects. Although recently several studies have shown the possibility to administer SLNs during pregnancy to vehicle mRNA to the placenta, data about the effect of premating exposure to SLNs on pregnancy outcome are scant. Considering that assumption of drug-delivering nanocarriers in reproductive age may potentially affect women’s reproductive health, the aim of the present study was to evaluate whether repeated oral administration of SLNs to female mice prior to mating would influence key pregnancy outcomes. For this purpose, SLNs melatonin loaded (SLN + mlt) or unloaded were orally administered to CD1 female mice at two different dosages—low (7.5 mg/kg) and high (750 mg/kg) —three times a week for 6 weeks. Females mice were mated and pregnancy was monitored from conception to delivery. All the assessed pregnancy parameters, including time to pregnancy, pregnancy duration, litter size, and the presence of any gross anomalies in the pups, and maternal key biochemical parameters were not significantly affected by SLN administration. Embryonic development was also evaluated and no effects on the number of implantation sites, fetus numbers, incidence of fetal resorptions, and measurements of crown-rump length, as well as fetal and placental weights, were observed in the treated mothers. The impact of SLNs on maternal intestinal barrier integrity and inflammation was assessed both in vivo in mice and in vitro using an intestinal epithelial barrier model by qRT-PCR. Results showed that unloaded SLNs, but not the SLN + mlt, affected intestinal barrier integrity. Although variation in the expression of inflammatory cytokines was recorded, this did not reflect in significant histological alterations and the integrity of the intestinal barrier was maintained. The in vitro model further confirmed the biocompatibility of SLNs, showing that both loaded and unloaded SLNs did not affect the integrity of the simulated intestinal epithelial barrier. In conclusion, these data suggest that administering SLNs, as a drug delivery vehicle, prior to conception does not affect either maternal health or fetal development, posing no risk to future pregnancy.